The Effects of Dietary Inositol on Dimensional Obsessive Compulsive Scale Score - Sahin Kaya, Aysel; Sarıteke, Yaprak; Özkan, Hüseyin Murat (Progress in Nutrition, 2021)
Objective: The aim of the study was to explain the relationship between obsessive and compulsive disorder scores of university students, inositol levels in their diet and Mediterranean diet compatibility and to use nutrients as a protective method for disease formation. Material and Methods: 168 volunteers from Tekirdağ Namık Kemal University School of Health, School of Health and Faculty of Medicine were subjected to a ‘nutritional habits form’ consisting of 13 questions, a ‘Mediterranean diet compliance scale’ consisting of 14 questions, a ‘nutrient consumption frequency questionnaire’ containing inositol-rich foods and a dimensional Obsessive Compulsive Disorder scale consisting of 20 questions in the 2019-2020 academic year. Results: Of the participants, 83.3% had a DOCS score below 40 while 16.7% had a score of 40 and above. Daily inositol intake was 1000 mg and more in the 63.1% of the participants and was below 1000 mg in 36.9%. A statistically significant relationship was found between the concerns about “germs and contamination,” “concerns about being responsible for harm, injury, or bad luck,” “concerns about symmetry, completeness, and the need for things to be ‘just right’” categories of the DOCS and the amount of daily inositol intake (p1000 mg or